Water purification using ultrasound waves: application and challenges. Issue 1 (1st January 2020) - Fetyan, Nashwa A. H.; Salem Attia, Tamer Mohamed
Abstract: Due to the scarcity of water resources and the harmful effects of sewage on water bodies, water purification becomes an important issue. The application of ultrasonic waves is a novel technique developed for water purification. This technology works as an advanced method of oxidation, contributing to the elimination of various types of contaminants. The basic principle of ultrasound is based on the destruction of both bacterial cells and difficult to- degrade organics. A brief overview of water purification methods, application of ultrasound, ultrasound waves theory and the benefits and drawbacks of using ultrasound waves in water purification will be discussed in this article. In addition, the role of ultrasound waves in the degradation of various organic contaminants, microbial pollutant disinfection, and other pollutants removal.